Full Functional Sex Reversal Achieved Through Silencing of MroDmrt11E Gene in Macrobrachium rosenbergii: Production of All-Male Monosex Freshwater Prawn - Xu, Hai-Jing; Chen, Yi-Lai; Wang, Yong-Mei; Luo, Jing-Yu; Li, Jian-Wen; Shen, Shuai-Qi; Yang, Jin-Shu; Ma, Wen-Ming (Frontiers in Endocrinology, 2022)
The freshwater prawn Macrobrachium rosenbergii is one kind of important economic aquaculture species and displays remarkable sexual dimorphism. The molecular mechanism of sexual differentiation in M. rosenbergii has been primarily unraveled through the research efforts of the androgenic gland and its related genes. However, the understanding of conserved genes involved in the molecular mechanism underpinning sex determination and sexual differentiation of M. rosenbergii is still fragmentary. MroDmrt11E is a member of the doublesex and mab-3 related transcription factor (Dmrt) gene family and is prominently expressed in testis. In the present study, in vivo knockdown of MroDmrt11E at the post-larva stage in male prawn induced a complete and functional sex reversal and achieved the production of an all-male mono-sex population. Furthermore, a great deal of new information of up-and down-regulation transcriptions involved in sexual differentiation of MroDmrt11E knockdown was enriched by comparative transcriptomic analysis. The effects of RNAi-mediated gene knockdown of MroDmrt11E on the differentially expressed and sexual-related candidate genes, such as transformer, fruitless, feminization, insulin-like androgenic gland gene, Dmrt gene family, were primarily focused and their possible molecular regulatory relationships in sexual differentiation were analyzed. Meanwhile, the response of primary KEGG biological pathways was investigated to expound the potential roles of MroDmrt11E in the male sexual differentiation, which provided a deeper understanding of the molecular regulatory network underlying sexual differentiation of M. rosenbergii. The finding provided a novel sexual manipulation technique through silencing of Dmrt gene family for achieving a complete and functional sex reversal and offered a new insight regarding the mechanism of the Dmrt gene family in the sexual differentiation of crustaceans.